INVESTIGATING THE ATTITUDE OF OFFA RESIDENTS IN KWARA STATE NIGERIA TOWARDS CLEAN WATER AND SANITATION (SDG6) - Okoji, Chukwudinma Taiwo; Adesina, Victoria Dolapo; Bisiriyu, Ganiyu; Umar, Aliu Faruk (African Journal of Social and Behavioural Sciences, 2025)
The Sustainable Development Goals (SDGs) were introduced in 2015 to achieve 17 global objectives. Among these, Goal 6, which focuses on Clean Water and Sanitation, aims to ensure access to adequate sanitation and sustainable water management for all by 2030. This study investigates the knowledge, perceptions, and attitudes of residents in Offa Local Government Area (LGA) toward achieving the targets of SDG 6 by 2030. A Survey Research Method was employed, utilising Purposive and Availability Sampling Techniques to gather responses from 176 participants through an e-questionnaire. The sample size was determined using the formula by Saunter et al. (2009). The findings indicated that residents of Offa hold a positive and forward-thinking attitude toward sustainable water and sanitation practices as they believed it is important for individuals to practice sustainable water management (x̅ = 4.76), support community initiatives aimed at improving water and sanitation practices (x̅ = 4.65). Additionally, the study revealed that their attitudes are closely linked to the effectiveness of existing government policies and interventions related to water and sanitation in the region, as the majority of the respondents (167) agreed that they have a positive attitude towards the realisation of SDG 6 on water and sanitation in Offa LGA. Based on these findings, the study recommends increased media campaigns across all Nigerian states to raise awareness of the benefits of clean water and sanitation, helping to reduce health risks and promote well-being for residents.